Impact Analysis of Strategic Policy of Natural Resources and Environment in the Indonesian Long-term Development Plan of 2005-2025 - Arif Haryana (Pusbindiklatren Bappenas, 2022)
The policy implementation under the Indonesian Long-term Development Plan (RPJPN) for the 2005-2025 period is currently in the final stage. It is thus necessary to evaluate the development and impacts of the strategic policy implementation in the area of Natural Resources and the Environment (NR&E). This paper attempted to evaluate the area of NR&E within the RPJPN of 2005-2025. It focused on identifying people's perceptions about the impacts of the strategic policy implementation in NR&E. The data were collected through a survey targeting all regions of Indonesia and analysed using the importance-Performance Analysis (IPA) method. The results of the analysis showed that strategic policy implementation in NR&E was rated as having a fairly good impact. It was indicated by an average aggregate impact indicator score of 3.61 on a Likert scale of 1-5. With regard to the impacts on the aspects of development, the strategic policies of NR&E had a relatively high impact on economic growth, food security, and energy security. However, the impacts on job creation and reduction of poverty were relatively lower. There is an indication that strategic policies in NR&E tend to be biased as they favour capital owners.